2010
DOI: 10.1007/s12070-010-0050-4
|View full text |Cite
|
Sign up to set email alerts
|

Speech Recognition Performance in Children with Cochlear Implants Using Bimodal Stimulation

Abstract: Cochlear implantees have considerably good speech understanding abilities in quiet surroundings. But, ambient noise poses significant difficulties in understanding speech for these individuals. Bimodal stimulation is still not used by many Indian implantees in spite of reports that bimodal stimulation is beneficial for speech understanding in noise as compared to cochlear implant alone and also prevents auditory deprivation in the un-implanted ear. The aim of the study is to evaluate the benefits of bimodal st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…The present results showed a small but significant bimodal benefit for tone recognition (largely due to improved recognition of tone 2), consistent with previous findings ([ 35 , 36 ]). However, there was no significant bimodal benefit for vowel, consonant, or sentence recognition in quiet, consistent with some previous studies [ 18 , 35 ]. Li et al [ 35 ] found a significant bimodal benefit for vowel recognition in quiet in adult Mandarin-speaking CI users, but not for tone or vowel recognition in quiet.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present results showed a small but significant bimodal benefit for tone recognition (largely due to improved recognition of tone 2), consistent with previous findings ([ 35 , 36 ]). However, there was no significant bimodal benefit for vowel, consonant, or sentence recognition in quiet, consistent with some previous studies [ 18 , 35 ]. Li et al [ 35 ] found a significant bimodal benefit for vowel recognition in quiet in adult Mandarin-speaking CI users, but not for tone or vowel recognition in quiet.…”
Section: Discussionsupporting
confidence: 92%
“…Li et al [ 35 ] found a significant bimodal benefit for vowel recognition in quiet in adult Mandarin-speaking CI users, but not for tone or vowel recognition in quiet. Rathna-Kumar et al [ 18 ] found a bimodal benefit for speech understanding in noise in India-speaking pediatric CI users, but not for speech understanding in quiet. Note that the variability in performance was reduced with the CI + HA, relative to CI-only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modern digital signal processing technology in HAs includes nonlinear, compression, multichannel, adaptive, noise reduction, feedback manager, directional microphones, multiple memories, etc. (5) . HAs with multiple compression channels are the predominant type of emerging technology in today's HA market.…”
Section: Introductionmentioning
confidence: 99%